Fire / 2. - Cashore, Kristin (Graceling Realm Series, 2009)
In a kingdom called the Dells, Fire is the last human-shaped monster, with unimaginable beauty and the ability to control the minds of those around her, but even with these gifts she cannot escape the strife that overcomes her world.